Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/cg501437g
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Cuboidal 15- and 16-Membered Water Clusters in Brucine 3.86-Hydrate, Water Release and Its Consequences

Abstract: Up to now, three brucine hydrates are known, brucine di-, tetra-, and 5.25-hydrate. All of them were obtained from solutions containing the additive diethanolamine, adenosine, and urea, respectively. Studying the role of the additives on crystallization of the brucine hydrates, we obtained a new, kinetically favored brucine 3.86-hydrate. In crystals of brucine 3.86-hydrate, large 15- and 16-membered water clusters of cuboidal topology are encapsulated in cages formed between honeycomb-like brucine layers. Dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…5 kJ mol –1 less stable than the global conformational energy minimum (see section 1.1 of the Supporting Information). So far, two anhydrous ( AH and AH LT ) and 20 solvate structures have been reported: four hydrates showing a different water:brucine ratio (2:1, 4:1, 3.86:1 and 5.25:1),55,58,59 and 16 solvates, including four mixed solvates 56,58,59,50,57…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5 kJ mol –1 less stable than the global conformational energy minimum (see section 1.1 of the Supporting Information). So far, two anhydrous ( AH and AH LT ) and 20 solvate structures have been reported: four hydrates showing a different water:brucine ratio (2:1, 4:1, 3.86:1 and 5.25:1),55,58,59 and 16 solvates, including four mixed solvates 56,58,59,50,57…”
Section: Resultsmentioning
confidence: 99%
“…The low temperature anhydrate ( AH LT ) has been reported to be enantiotropically related to AH . The AH to AH LT transformation occurs upon cooling at −24 °C and the reversible AH LT to AH back transformation at 36 °C upon heating 55. Slurry experiments in organic solvents showed that the thermodynamic transition point between the polymorphic pair AH / AH LT is lower than 10 °C 37…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such channels can be not only dehydrated but also substituted with other solvents [300,301]. The solid dehydration with prominent atomic movement traced with single-crystal or powder X-Ray diffraction can shed light on a more complex mechanism of water loss [302][303][304][305][306]. Various mobility of the water clusters incorporated within the pores and H-bonding waters that structure these pores was demonstrated in Refs.…”
Section: Analysis Of Solvent Associatesmentioning
confidence: 97%